Acute responses in blood flow restriction low-intensity aerobic training: A meta-analysis - Sabino de Queiros, S.; Rolnick, N.; Sabag, A.; Martins de França, I.; Wilde, P.; Vieira, J. G.; Machado Reis, V.; Formiga, M. F.; Guilherme de Araújo Tinôco Cabral, B.; Moreira Silva Dantas, P. (International Journal of Sports Medicine, 2023)
The purpose was to determine the effect low-intensity training with blood flow restriction (LI-BFR) versus high-intensity aerobic training (HIT) on acute physiological and perceptual responses. The Cumulative Index to Nursing and Allied Health Literature, National Library of Medicine, Scopus, SPORTDiscus and Web of Science databases and the reference list of eligible studies were consulted to identify randomized experimental studies, published until July 4, 2022, that analyzed physiological or perceptual responses between LI-BFR versus HIT in healthy young individuals. Mean difference (MD) and standardized mean difference (SMD) were used as effect estimates and random effects models were applied in all analyses. Twelve studies were included in this review. During exercise sessions, HIT promoted higher values of heart rate (MD=28.9 bpm; p<0.00001; I 2 =79%), oxygen consumption (SMD=4.01; p<0.00001; I 2 =83%), ventilation (MD=48.03 l/min; p=0.0001; I 2 =97%), effort (SMD=1.54; p=0.003; I 2 =90%) and blood lactate (MD=3.85 mmol/L; p=0.002; I 2 =97%). Perception of pain/discomfort was lower in HIT (SMD=-1.71; p=0.04; I 2 =77.5%). In conclusion, LI-BFR promotes less pronounced physiological responses than HIT but with greater perception of pain.